Obligasi Dan Sukuk Dalam Perspektif Keuangan Islam (Suatu Kajian Perbandingan) - Zubair, Muhammad Kamal (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
This  article  study  about  sukuk  is  known  as  sharia bonds with compare to obligation as the investment instrument in capital market.  Sukuk investment is  often regard as identical with obligation. There are number of basic differences between the  two  instrument,  that  is  the  use  of  sukuk  instruments  in investment  the  profit  of  which  is  divided  with  profit  sharing, sukuk  needs  to  have  an  underlying  transaction  in  the  form  of tangible assets and sukuk use religious advice that govern syariah bond.